IMPLEMENTASI PENGAWASAN DPRD PROVINSI BALI TERHADAP KEWENANGAN KPID BALI DALAM MENETAPKAN P3SPS LOKAL - Anak Agung Gede Ananta Wijaya Sahadewa (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2020)
Anak Agung Gede Ananta Wijaya SahadewaFakultas Hukum Universitas Brawijaya Jl. MT. Haryono No.169 MalangEmail: gungdenanta@gmail.comAbstrak Penelitian ini bertujuan untuk memahami dan menganalisis pengawasan yangdilakukan DPRD Provinsi Bali terhadap Kewenangan Komisi Penyiaran Daerah Bali(KPID Bali) dalam menetapkan Pedoman Perilaku Penyiaran dan Standar ProgramSiaran (P3SPS) Lokal. Jenis penelitian ini ialah yuridis empiris dengan menggunakanpendekatan penelitian yuridis sosiologis. Berdasarkan hasil penelitian ini,Implementasi Pengawasan DPRD Provinsi Bali terhadap Kewenangan KPID Bali dalammenetapkan Pedoman Perilaku Penyiaran dan Standar Program Siaran (P3SPS) Lokalyang seuai dengan pasal 7 dan pasal 8 Undang-undang Nomor 3 Tahun 2002 TentangPenyiaran sudah dilaksanakan tetapi belum maksimal dan dapat dikatakan peraturantersebut belum efektif karena KPID Bali belum melaksanakan kewenangannya secarapenuh serta adanya hambatan-hambatan bagi KPID dalam melaksanakankewenangannya untuk menetapkan Pedoman Perilaku Penyiaran dan StandarProgram Siaran (P3SPS) Lokal yaitu masalah anggaran. Anggaran yang terbatasmembuat KPID Bali sulit untuk membuat peraturan tersebut dan terbatasnya SDMyang ada di KPID Bali membuat DPRD Provinsi Bali kesulitan dalam mengatasi permasalahan di KPID Bali.Kata Kunci: DPRD Bali, KPID Bali, Pengawasan, P3SPS AbstractThis thesis studies the implementation of Supervision performed by Regional House ofRepresentatives (hereinafter DPRD) of the Province of Bali over Authority of IndonesianBroadcasting Commission at Regional Level (hereinafter KPID) Bali to perform Guidelinesof Broadcasting Protocol and Standard of Broadcast Program (hereinafter P3SPS). Theresearch topic departs from the study of Article 7 paragraph 4 of Law Number 32 of 2002concerning Broadcasting implying that KPID is under the supervision of DPRD and Article 8paragraph 2 of Law Number 32 concerning Broadcasting stating that IndonesianBroadcasting Commission (KPI) holds an authority to set and arrange P3SPS.With the above research background, this research is more focused on studying thefollowing problems: (1) how is the supervision over Broadcast Commission of Baliperformed by DPRD Bali regarding P3SPS? (2) What are the hampering factors faced by theDPRD of the Province of Bali in delivering the supervision over KPID Bali regarding theimplementation of P3SPS?This research employed empirical juridical method and socio-juridical approach.Primary and secondary data was analysed by means of descriptive-qualitative analysismethod. All the data was obtained from an interview with the member of Commission I ofDPRD of the Province of Bali and Commissioner of KPID Bali, observation, and literaturereview.The research has found out the implementation of the supervision as mentioned abovehas been relevant to Article 7 and Article 8 of Law Number 3 of 2002 and implementedaccordingly but not optimally. In other words, the policy concerned is not effectivelyimplemented since KPID has not fully performed its authority, in addition to impedingfactors faced by the KPID when it executes its authority regarding P3SPS specifically relatedto budget. Limited budget seems to present a barrier to making a regulation, and limitedhuman resources in KPID Bali also presents a problem for the DPRD of Bali to tackle theproblem arising in KPID Bali.